2011
DOI: 10.1111/j.1600-0714.2011.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori in the oral cavity and gastric mucosa: a meta-analysis

Abstract: There is a close relation between the infection of H. pylori in the oral cavity and stomach. H. pylori in the oral cavity are more difficult to be eradicated than in the stomach. It may be a source of reinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 29 publications
2
55
0
2
Order By: Relevance
“…Some PCR studies found H. pylori DNA in samples from oral cavities, but overall, reports of live H. pylori are very rare and inconclusive [33] . In light of this literature review, we agree with Zou and Li [34] and their report that H. pylori can be identified unequivocally only through the use of direct cultures. This limitation exists because erroneous PCR results can result from the presence of transient H. pylori in…”
Section: Root Canals and Oral Mucosasupporting
confidence: 89%
“…Some PCR studies found H. pylori DNA in samples from oral cavities, but overall, reports of live H. pylori are very rare and inconclusive [33] . In light of this literature review, we agree with Zou and Li [34] and their report that H. pylori can be identified unequivocally only through the use of direct cultures. This limitation exists because erroneous PCR results can result from the presence of transient H. pylori in…”
Section: Root Canals and Oral Mucosasupporting
confidence: 89%
“…However, there are some problems with this treatment, such as patient compliance, antibiotic resistance, and high cost, resulting in relapse after a short period in about 15% to 30% of patients (9)(10)(11)(12). There is some evidence of the presence of H. pylori in the oral cavity, which a recent meta-analysis related to gastric colonization and possible reinfection (13,14). The presence of H. pylori in tonsils is controversial (15)(16)(17); if confirmed, it could help further understanding of H. pylori transmission and reinfection.…”
mentioning
confidence: 99%
“…Varios estudios han demostrado la presencia de H. pylori simultáneamente en cavidad oral y mucosa gástrica, mostrando diferentes prevalencias, dependiendo de la población estudiada, la selección de la muestra y técnicas de detección de la bacteria [26][27][28][29][30][31][32][33]40 . Mapstone 41 , demostró que la presencia de H. pylori en la boca de pacientes dispépticos es importante para su diseminación y considera la cavidad oral una potencial fuente de reinfección luego de la erradicación del microorganismo del estómago.…”
Section: Discussionunclassified
“…Algunos autores han encontrado una asociación entre la presencia de H. pylori en mucosa gástrica y oral [26][27][28][29][30][31][32][33] . En una investigación previa realizada por nuestro grupo, se observó la co-existencia de la bacteria en ambas localizaciones mediante RPC en tiempo real (RPC-TR) 34 .…”
Section: +16unclassified